Introduction to the Operation Room Management technology: Interrupted Time Series analysis in an urban acute care hospital facility in Rome, Italy - Marte, Mattia; Piunno, Gaia; Furia, Giuseppe; Vinci, Antonio; Ingravalle, Fabio; Ungaro, Stefano; Bardhi, Dorian; D'Agostino, Gennaro; Chierchini, Patrizia; De Vito, Corrado; Maurici, Massimo (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The surgical pathway represents a fundamental process in hospital productivity, and its digitalization is a major focus for hospital management. ASL Roma 1 health authority has taken up this digitalization challenge by introducing an Operation Room Management (ORM) system within the operating block of one of its hospital facilities in 2022. Study Design. Interrupted Time Series analysis. Methods.To evaluate the impact of Operation Room Management system adoption, data on surgery were collected from all inter- ventions performed during two periods: January-June 2019 and January-June 2023. Analysis of the Operation Room Management system utilization rate since its introduction was performed, to estimate staff adaptation to the new software. Results. As of June 2023, paper-registered interventions were 9%, nearing 100% for elective procedures only. The difference between the average intervention times was significantly in favor of the Operation Room Management cohort when restricting the analysis to Orthopedics (-9.02 minutes, p=0.006) and Surgery (8.47 min, p = 0.03). There was a modest but significant impact of Operation Room Management on the ‘entering Operation Room to Incision’ time (5 min, p < 0.01). Conclusion. Overall, the adoption of the Operation Room Management did not worsen process outcomes. Operation Room Mana- gement offers advantages in real-time data quality, integrated with territorial and hospital platforms, contributing to a favorable cost-benefit assessment of digitalization.